Uji Normalitas Kolmogorov-Smirnov Menggunakan Microsoft Excel - Bisma, Muhammad Ardhya; Sanggala, Ekra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
One important thing in conducting statistical analysis is the normality test. The purpose of the normality test is to determine whether the data to be used in the research follows a normal distribution or does not follow a normal distribution. One of the normality tests is the Kolmogorov-Smirnov Normality Test. Microsoft Excel is equipped with Statistical Function. Thus the Kolmogorov-Smirnov Normality Test can be done with the help of Microsoft Excel. An example of a case in the form of bull mass data with a sample size of 90 has passed the normality test using the Kolmogorov-Smirnov method, the results of which are that the data is normally distributed.